Nilai Manfaat Ekonomi Konservasi Borobudur - Soeroso, Amiluhur; Susilo, Y. Sri (UI Scholars Hub, 2010)
The purpose of this study is to select the management zone to avoid the deterioration of environmental goods, by conducting comparative value of the economic benefits of conservation between management focused on the monument that pay attention only to the entire ecosystem of Borobudur Regions. Two hundred tourists who came to Borobudur or Jogjakarta were obtained as samples. Data were collected using interviews with structured questionnaire. Afterward, we used contingent valuation method (CVM) to calculate the value of the economic benefits and we measured the total value of the individual consumer's willingness to conserve the heritage under several scenarios of hypothetical market. The results testify that the value of theeconomic benefits of Borobudur area conservation reached US4.2 billion per annum or around IDR40.1 trillion. Thisvalue reflects that the area of Borobudur is important to be preserved. Such values can be operationally useful when planning and management have been conducted comprehensively. The implication of this is that government should forma new governing body that is integrated in one management, holistic, involving multi-stakeholders both central and local governments and local communities. Organizations like these need to be run with the principle of shared responsibility and independence in .financial. Therefore, as a World Heritage icon, the vision of the management of Borobudur area was needed to experience metamorphosis, from initially focus on short-term profits through increased tourism market, shifted to the achievement of long-term prosperity based conservation and education.